IL-27 posttranslationally regulates Y-box binding protein-1 to inhibit HIV-1 replication in human CD4+ T cells. (1st October 2019) - Poudyal, Deepak; Yang, Jun; Chen, Qian; Goswami, Suranjana; Adelsberger, Joseph W.; Das, Sudipto; Herman, Andrew; Hornung, Ronald L.; Andresson, Thorkell; Imamichi, Tomozumi
Abstract : Objectives: IL-27 is known as an antiviral cytokine that inhibits HIV, hepatitis C virus, and other viruses. We have previously demonstrated that, IL-27 posttreatment after HIV-infection inhibits viral replication in primary CD4 + T cells. Design: Here, we evaluated the anti-HIV effect of IL-27 pretreatment in CD4 + T cells from healthy donors prior to HIV infection with HIVNL4.3 or vesicular stomatitis virus G glycoprotein (VSV-G)-pseudotyped HIV-luciferase virus (HIV-LUC-V). Methods: IL-27-treated CD4 + T cells were infected with HIVNL4.3 or HIV-LUC-V and assessed the anti-HIV effect. HIV infection was monitored by p24 antigen ELISA or luciferase assay. HIV fusion/entry and uncoating were determined by BlaM-Vpr assay and HIV fate of capsid and/or HIV Entry/Uncoating assay based on core-packaged RNA availability and Translation assay, respectively. HIV proviral copy number was determined by real-time PCR. Gene expression profile from IL-27-pretreated CD4 + T cells was determined using Genechip array. Posttranslational modification of global proteins from IL-27-pretreated CD4 + T cells was determined by a combination of 2-dimensional difference-in-gel-electrophoresis (2D-DIG), western-blot and protein mass spectrometry. Results: IL-27 pretreatment inhibited HIVNL4.3 and HIV-LUC-V infection in CD4 + T cells. HIV copy assay demonstrated that IL-27-treatment suppressed an early step of reverse transcription during HIV infection. A combination of 2D-DIG-electrophoresis and western blot assays demonstrated that IL-27-treatment induces a change in posttranslational modification of Y box binding protein-1 (YB-1). Overexpression of domain negative YB-1 mutants illustrated that a residue Lysine at 118 plays a key role in supporting HIV infection in CD4 + T cells. Conclusion: IL-27-pretreatment inhibits HIV-1 infection by suppressing an HIV-reverse transcription product formation/uncoating step by suppressing the acetylation of YB-1 in primary CD4 + T cells. Abstract : Supplemental Digital Content is available in the text